Metamaterials History, Current State, Applications, and Perspectives - Kuznetsov, Aleksey (IntechOpen, 2023)
Metamaterials possess various properties of high interest not found in naturally occurring materials. They are built of specially designed assemblies of multiple elements arranged in repeating patterns with size scales smaller than the wavelengths of the phenomena to influence. Metamaterials have versatile applications in different areas of technology. Their research is an interesting and promising interdisciplinary area of science and technology involving various fields of knowledge. This book broadens the knowledge of metamaterials, highlighting their known types and applications and analyzing their use in antenna performance enhancement, polarization conversion, radar cross-section reduction, wave absorption, and electromagnetic and acoustic absorbers.